A kind of calcium silicate glass ceramic and preparation method thereof

By using SiO2 and CaO to form β-silica-calcium glass ceramics, the problem of high lithium content in dental microcrystalline glass products is solved, the hardness and cutting performance are improved, the fluctuations in production costs are reduced, and it is suitable for dental restorations. .

CN116444159BActive Publication Date: 2025-01-14FUZHOU YUEYA TIMES BIOTECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310392328.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-13
Publication Date
2025-01-14
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

The high content of lithium elements in existing dental microcrystalline glass products leads to fluctuations in production costs and is difficult to replace. Traditional lithium disilicate materials cannot maintain sufficient strength and cutting performance after the lithium element is reduced.

Method used

SiO2 and CaO are used as the main raw materials to form β-silicaite as the main crystal phase. By adjusting the content of Al2O3, MgO/BaO/ZnO and alkali metal oxides in the formula, the lithium content is reduced, and high-temperature melting and heat treatment are used. Form a silicate glass ceramic with high hardness and cutting properties.

Benefits of technology

Dental microcrystalline glass ceramics without or only trace amounts of lithium elements have a hardness of 150-200MPa and good cutting performance. They are suitable for dental restorations, reduce their dependence on lithium elements, and have a more stable production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005106523510000021
    Figure GDA0005106523510000021
  • Figure GDA0005106523510000022
    Figure GDA0005106523510000022
  • Figure GDA0005106523510000023
    Figure GDA0005106523510000023
Patent Text Reader

Abstract

The present invention relates to a calcium silicate glass ceramic and a preparation method thereof. The calcium silicate glass ceramic has the following composition in weight percent: SiO 2 55~75, CaO13~22, Al 2 O 3 4~12, ZnO1~8, MgO / BaO1~8, alkali metal oxides 1~8, Li 2 O<1, colorant 0.5-1.5. The main crystalline phase of the calcium silicate glass ceramic is β calcium silicate (CaO.SiO 2 ), the restoration can be used directly after cutting and polishing, without the need for secondary sintering; it is more suitable for use as intra-crown restorations, inlays, high onlays, inlay crowns, veneers, etc. Moreover, the calcium silicate glass ceramic component in this invention does not contain or only contains trace amounts of Li, has low cost, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dental embedded restorative material, in particular to calcium-silicate glass ceramics and a preparation method thereof. Background Art

[0002] In recent years, lithium disilicate glass-ceramics have been increasingly used in dental all-ceramics materials, and have almost occupied the entire dental glass-ceramics market. However, with the development of the electric vehicle industry, the demand for power batteries is increasing day by day; the price of lithium carbonate required for power batteries has skyrocketed. This material is one of the important raw materials for lithium disilicate glass-ceramics. Therefore, a dental glass-ceramics product that does not contain the Li element has an important market prospect.

[0003] The principle of traditional lithium disilicate dental glass-ceramics is to cut glass-ceramics with low strength while ensuring machinability (glass-ceramics with lithium metasilicate as the main crystal phase) and sinter after cutting to perform crystal phase conversion (after conversion, the main crystal phase is lithium disilicate). At this time, the strength of the glass-ceramics is greatly increased, reaching the range of 350MPa-400MPa. Such glass-ceramics have a wide range of indications and can be used as crowns for posterior teeth. Therefore, the Li element plays an important role in dental micro-glass products. If the Li element is reduced, lithium metasilicate cannot be used as the main crystal phase of the material. Therefore, it is necessary to select a crystal phase with other elements as the main components as the main crystal phase of the restorative material, which will bring about a great change in the material properties.

[0004] Patent application CN115093119A discloses a method for preparing lithium disilicate dental glass-ceramics, comprising the following steps: 1) SiO 2 , Li 2 CO 3 、Na 2 CO 3 , K 2 CO 3 NH 4 H 2 PO 4 、Al 2 O 3 、ZrO 2 、CeO 2 、V 2 O 5 , Tb 2 O 3 and Y 2 O 3 Mix according to the proportion, ball-mill evenly and dry; then pre-sinter, calcine, melt and quench to obtain glass frit;

[0005] 2) drying the obtained glass frit, crushing it in a ball mill, and sieving it to obtain lithium disilicate glass powder;

[0006] 3) placing the dental glaze powder and the obtained lithium disilicate glass powder in a ball mill in a certain proportion and mixing them;

[0007] 4) putting the mixed powder obtained in step 3) into a mold, placing it in a vacuum hot pressing sintering furnace for sintering, then cooling it in the furnace, and demolding it at room temperature to obtain a lithium disilicate glass-ceramic sheet;

[0008] 5) The obtained lithium disilicate glass-ceramic sheet is placed in a mold, stacked into a layered structure with a certain thickness, and then placed in a vacuum hot-pressing sintering furnace for sintering, and then cooled with the furnace and demolded at room temperature to obtain a lithium disilicate glass-ceramic block for dentistry. The obtained glass frit has Li 2 The mass percentage of O is 13%.

[0009] In the above scheme, Li in glass ceramics 2 The mass percentage of O is higher than 10%, and the production cost is still affected by the fluctuation of lithium material prices. Summary of the invention

[0010] The purpose of the present invention is to overcome the problem of high lithium content in existing dental glass-ceramics products and provide a calcium silicate glass ceramic, the main crystal phase of which is β calcium silicate, and the main component of the glass contains no or only a trace amount of Li element. The restoration can be cut and polished and used directly without secondary sintering.

[0011] In order to reduce the lithium content in the product, this application uses SiO 2 As the main raw materials, Al2O3 and CaO are the basis for forming the main crystalline phase β-calcium silicate in glass ceramics. In the formula system of the present invention, Al2O3 is mainly used to increase the glass transition temperature and softening point of glass ceramics, and improve the chemical stability of glass ceramics. MgO / BaO / ZnO mainly plays a role of fluxing and can also improve chemical stability. The main function of alkali metal oxides Li2O / Na2O / K2O is to reduce the high temperature viscosity of glass, and is also used to adjust the thermal expansion coefficient of glass ceramics.

[0012] The specific plan is as follows:

[0013] A calcium silicate glass-ceramic, comprising the following composition in wt %:

[0014]

[0015] Further, the following composition of the limestone glass ceramic is measured in weight %:

[0016]

[0017] The alkali metal oxide is Li 2 O、Na 2 O.K2 At least one of O; or

[0018] The following composition in % by weight:

[0019]

[0020]

[0021] The alkali metal oxide is Li 2 O、Na 2 O.K 2 O at least one; or, the following composition in wt %:

[0022]

[0023] The alkali metal oxide is Li 2 O、Na 2 O.K 2 O at least one; or, the following composition in wt %:

[0024]

[0025] The alkali metal oxide is Li 2 O、Na 2 O.K 2 At least one of O.

[0026] Further, the following composition of the limestone glass ceramic is measured in weight %:

[0027]

[0028]

[0029] The alkali metal oxide is Li 2 O、Na 2 O.K 2 O at least one; or, the following composition in wt %:

[0030]

[0031] The alkali metal oxide is Li 2 O、Na 2 O.K 2 O at least one; or, the following composition in wt %:

[0032]

[0033] The alkali metal oxide is Li 2 O、Na 2 O.K2 At least one of O.

[0034] Further, the calcium silicate glass ceramic has the following composition in weight %:

[0035]

[0036]

[0037] The alkali metal oxide is Na 2 O.K 2 At least one of O; or

[0038] The following composition in % by weight:

[0039]

[0040] The alkali metal oxide is Na 2 O.K 2 At least one of O.

[0041] Furthermore, the colorant component includes V 2 O 5 , Tb 4 O 7 , Er 2 O 3 , Fe 2 O 3 、Eu 2 O 3 , Pr 6 O 11 、MnO 2 、TiO 2 One or more of the following.

[0042] Furthermore, the calcium silicate glass ceramic has at least one of the following (1) to (5):

[0043] (1) The amount of β-calcium sulphate crystals in the calcium sulphate glass-ceramics accounts for 20% to 60% of the total mass;

[0044] (2) The visible light transmittance of the calcium silicate glass ceramic is 25-40%;

[0045] (3) The crystal particles of the calcium silicate glass ceramic are fine and the color is the same as or similar to the color of human real teeth;

[0046] (4) The hardness of the calcium silicate glass ceramic is 150-200 MPa;

[0047] (5) The calcium silicate glass ceramic is cut at a spindle speed of 60,000 rpm and a cutting accuracy of 0.02 mm without edge chipping or jaggedness.

[0048] The present invention also protects a method for preparing the limestone glass ceramic, comprising the following steps:

[0049] 1) Weighing and mixing: weigh the basic glass components, mix the glass components evenly by ball milling, and then degas;

[0050] 2) Melt it into glass liquid in a high temperature furnace;

[0051] 3) After the glass liquid is melted evenly, it is poured into the required mold and demolded to obtain a transparent glass block;

[0052] 4) The glass block is subjected to annealing, nucleation and heat treatment to obtain the limestone glass ceramic.

[0053] Furthermore, the melting temperature in step 2) is 1500-1700° C., and the melting time is 60-300 min;

[0054] Preferably, the annealing temperature in step 4) is 500-600° C., the nucleation time is 60-360 min, the heat treatment temperature is 1000-1200° C., and the heat treatment time is 1-240 min.

[0055] The present invention also protects the use of the calcium-silicate glass-ceramic in dental restorations, especially for making at least one of intra-coronal restorations, inlays, onlays and veneers.

[0056] The present invention also protects a dental restoration comprising the limestone glass ceramic.

[0057] Beneficial effects:

[0058] In the present invention, the content ratio of each component is adjusted to control the number and size of β-calcium mortar, which not only ensures that the glass ceramic has good cutting performance, but also can adjust the transmittance and color of the sample. DETAILED DESCRIPTION

[0059] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the embodiments, if specific techniques or conditions are not indicated, the techniques or conditions described in the literature in this area or the product specifications are carried out. The reagents used or the instruments that are not indicated by the manufacturer are all conventional products that can be obtained commercially. In the following embodiments, if not specifically stated, "%" refers to weight percentage, and parts refer to weight parts.

[0060] The glass transmittance test is carried out using a glass transmittance meter. Transparency over 45% is considered high transmittance, and transmittance below 45% is considered low transmittance.

[0061] Color is observed with the naked eye. There are currently two common colorimetric plates in the world:

[0062] Color plate 1: Ivocar A-D20 color plate;

[0063] Color plate 2: VITA color plate;

[0064] The present invention determines the color number by comparing the color of the original tooth with the color comparison plate by naked eyes, and mixes different colorants according to the color number of the color comparison plate 1 to achieve color difference.

[0065] Example 1

[0066] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0067] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate, respectively.

[0068] The alkali metal oxide can be one or more of potassium oxide, sodium oxide and lithium oxide, which are introduced by potassium carbonate, sodium carbonate and lithium carbonate respectively. 2 O 5 , Tb 4 O 7 , Er 2 O 3 The three are mixed in a mass ratio of 1:1:1 before use.

[0069] After mixing, the ingredients were ball milled for 8 hours to mix evenly, degassed in a muffle furnace, and placed in a high-temperature melting furnace to melt at 1600°C for 2 hours.

[0070] The obtained melt is poured and demolded, annealed at 550° C., nucleated at 740° C. / 60 min, and heat treated at 1000° C. / 2 h to obtain the β-calcium silicate glass ceramic.

[0071] Table 1 Raw material usage (weight %)

[0072]

[0073] The prepared calcium silicate glass ceramics were tested and found to have fine crystal particles and a hardness of 150MPA-200MPA. When cut under pressure (spindle speed within 60000rmp, cutting accuracy 0.02mm), there was no edge chipping and no serration, and the cutting performance was good.

[0074] Embodiment 2:

[0075] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0076] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0077] The obtained melt is poured and demolded, annealed at 550° C., nucleated at 740° C. / 60 min, and heat treated at 1000° C. / 2 h to obtain the β-calcium silicate glass ceramic.

[0078] The prepared calcium silicate glass ceramics were tested and found to have fine crystal particles and a hardness of 150MPA-200MPA. When cut under pressure (spindle speed within 60000rmp, cutting accuracy 0.02mm), there was no edge chipping and no serration, and the cutting performance was good.

[0079] Embodiment 3:

[0080] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0081] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0082] The obtained melt is poured and demolded, annealed at 550° C., nucleated at 740° C. / 60 min, and heat treated at 1000° C. / 2 h to obtain the β-calcium silicate glass ceramic.

[0083] The prepared calcium silicate glass ceramics were tested and found to have fine crystal particles and a hardness of 150MPA-200MPA. When cut under pressure (spindle speed within 60000rmp, cutting accuracy 0.02mm), there was no edge chipping and no serration, and the cutting performance was good.

[0084] Embodiment 4:

[0085] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0086] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0087] The obtained melt is poured and demolded, annealed at 550° C., nucleated at 740° C. / 60 min, and heat treated at 1000° C. / 2 h to obtain the β-calcium silicate glass ceramic.

[0088] The prepared calcium silicate glass ceramics were tested and found to have fine crystal particles and a hardness of 150MPA-200MPA. When cut under pressure (spindle speed within 60000rmp, cutting accuracy 0.02mm), there was no edge chipping and no serration, and the cutting performance was good.

[0089] Embodiment 5:

[0090] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0091] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0092] The obtained melt is poured and demolded, annealed at 550°C, nucleated at 740°C / 60min, and heat treated at 1000°C / 2h to obtain the β-calcium silicate glass ceramic.

[0093] The prepared calcium silicate glass ceramics were tested and found to have fine crystal particles and a hardness of 150MPA-200MPA. When cut under pressure (spindle speed within 60000rmp, cutting accuracy 0.02mm), there was no edge chipping and no serration, and the cutting performance was good.

[0094] Comparative Example 1:

[0095] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0096] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1700°C for 300 minutes.

[0097] The obtained melt is poured and demolded, annealed at 550°C, nucleated at 740°C / 60min, and heat treated at 1000°C / 2h to obtain the β-calcium silicate glass ceramic.

[0098] The main problem of this comparative example is that the SiO2 content is too high. Therefore, even if the glass is melted at 1700°C for 300 minutes, a uniformly melted glass block cannot be obtained, and the product is a glass block with uneven color.

[0099] Comparative Example 2:

[0100] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0101] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0102] The obtained melt is poured and demolded, annealed at 550°C, nucleated at 740°C / 60min, and heat treated at 1000°C / 2h to obtain the β-calcium silicate glass ceramic.

[0103] The main problem of this comparative example is that the content of the colorant is too low, so the color of the molten glass block is too light, and compared with human real teeth, the color cannot meet the aesthetic requirements of dental restorations.

[0104] Comparative Example 3:

[0105] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0106] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0107] The obtained melt is poured and demolded, annealed at 550°C, nucleated at 740°C / 60min, and heat treated at 1000°C / 2h to obtain the β-calcium silicate glass ceramic.

[0108] The main problem of this comparative example is that the CaO content is too low. Therefore, the proportion of the generated β-calcium silicate crystal phase is insufficient, resulting in increased glass transparency. The glass transparency is >50%, which cannot meet the aesthetic requirements of dental restorations.

[0109] Comparative Example 4:

[0110] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0111] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0112] The obtained melt is poured and demolded, annealed at 550°C, nucleated at 740°C / 60min, and heat treated at 1000°C / 2h to obtain the β-calcium silicate glass ceramic.

[0113] The main problem of this comparative example is that the alkali metal content is too high. Therefore, the softening point of the generated glass is too low, and it deforms and softens during heat treatment. If the heat treatment temperature is lowered, it is not conducive to the formation of β-calcium silicate, and instead it is replaced by impurities such as lithium disilicate and feldspar, which cannot be used as a dental restoration material.

[0114] Comparative Example 5:

[0115] A lithium disilicate glass ceramic and a preparation method and application thereof, the specific steps are as follows:

[0116] The ingredients were prepared according to the ingredient list in Table 1. The raw materials were analytically pure, and potassium oxide, sodium oxide and lithium oxide were introduced from potassium carbonate, sodium carbonate and lithium carbonate respectively. After the ingredients were prepared, they were ball milled for 8 hours to mix evenly and degassed in a muffle furnace. They were placed in a high-temperature melting furnace and melted at 1600°C for 2 hours.

[0117] The obtained melt is poured and demolded, annealed at 550° C., nucleated at 740° C. / 60 min, and heat treated at 1000° C. / 2 h to obtain the β-calcium silicate glass ceramic.

[0118] The main problem of this comparative example is that the aluminum oxide content is too low, so the resulting glass transition temperature is too low, and the softening point is too low, and it deforms and softens during heat treatment. If the heat treatment temperature is lowered, β-calcium silicate cannot be formed and cannot be used as a dental restoration material.

[0119] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0120] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0121] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A calcium silicate glass ceramic, characterized in that: The composition includes the following in weight %: SiO255~75 CaO13~22 Al2O34~12 ZnO1~8 MgO / BaO1~8 Alkali metal oxides 1~8 Li2O<1 Pigment 0.5~1.

5.

2. The calcium silicate glass ceramic according to claim 1, characterized in that: The composition includes the following in weight %: SiO260~70 CaO15~18 Al2O34~12 ZnO1~8 MgO / BaO1~8 Alkali metal oxides 1~5 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O; or The composition includes the following in weight %: SiO260~70 CaO15~18 Al2O35~10 ZnO1~8 MgO / BaO1~8 Alkali metal oxides 1~5 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O; or The composition includes the following in weight %: SiO255~75 CaO13~22 Al2O35~10 ZnO1~8 MgO / BaO1~8 Alkali metal oxides 1~5 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O; or The composition includes the following in weight %: SiO255~75 CaO13~22 Al2O34~12 ZnO3~5 MgO / BaO3~5 Alkali metal oxides 1~8 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O.

3. The calcium silicate glass ceramic according to claim 1, characterized in that: The composition includes the following in weight %: SiO260~70 CaO15~18 Al2O35~10 ZnO3~5 MgO / BaO3~5 Alkali metal oxides 1~8 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O; or The composition includes the following in weight %: SiO260~70 CaO15~18 Al2O35~10 ZnO3~5 MgO / BaO3~5 Alkali metal oxides 1~5 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O; or The composition includes the following in weight %: SiO260~65 CaO15~18 Al2O35~10 ZnO3~5 MgO / BaO3~5 Alkali metal oxides 1~5 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Li2O, Na2O, and K2O.

4. The calcium silicate glass ceramic according to claim 1, characterized in that: The composition includes the following in weight %: SiO260~65 CaO15~18 Al2O35~10 ZnO3~5 MgO / BaO3~5 Alkali metal oxides 1~5 Li2O<1 Pigment 0.5~1.5; The alkali metal oxide is at least one of Na2O and K2O.

5. The calcium silicate glass ceramic according to any one of claims 1 to 4, characterized in that: The pigment components include V2O5, Tb4O7, Er2O3, Fe2O3, Eu2O3, Pr6O 11 , MnO2, TiO2 or more.

6. The calcium silicate glass ceramic according to any one of claims 1 to 4, characterized in that: Having at least one of the following (1) to (5): (1) The amount of β-calcium phosphate crystals in the calcium phosphate glass-ceramic accounts for 20% to 60% of the total mass; (2) The visible light transmittance of the calcium silicate glass ceramic is 25-40%; (3) The crystal particles of the calcium silicate glass ceramic are fine, and the color is the same as or similar to the color of human real teeth; (4) The hardness of the calcium silicate glass ceramic is 150-200 MPa; (5) The calcium silicate glass ceramic is cut at a spindle speed of 60,000 rpm and a cutting accuracy of 0.02 mm without edge chipping or sawtooth.

7. The method for preparing the limestone glass-ceramic according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Weighing and mixing: weigh the basic glass components, mix them evenly with ball mill and then degas; 2) Melt it into molten glass in a high temperature furnace; 3) After the glass liquid is melted evenly, it is poured into the required mold and demolded to obtain a transparent glass block; 4) The glass block is subjected to annealing, nucleation and heat treatment to obtain the calcium silicate glass ceramic.

8. The method for preparing the limestone glass ceramic according to claim 7, characterized in that: The melting temperature in step 2) is 1500-1700° C. and the melting time is 60-300 min.

9. The method for preparing the limestone glass ceramic according to claim 8, characterized in that: In step 4), the annealing temperature is 500-600° C., the nucleation time is 60-360 min, the heat treatment temperature is 1000-1200° C., and the heat treatment time is 1-240 min.

10. Use of the calcium silicate glass ceramic according to any one of claims 1 to 6 in dental restorations.

11. The use of the calcium silicate glass ceramic in dental restorations according to claim 10, characterized in that: Used to make at least one of intracrown restorations, inlays, and veneers.

12. A dental restoration, characterized in that: The invention relates to a calcium silicate glass-ceramic comprising the calcium silicate glass-ceramic according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of lithium disilicate dental microcrystalline glass

    CN115093119A

  • Lithium silicate glass ceramic, preparation method thereof and obtained prosthesis

    CN114644459A

  • Glass ceramic, preparation method thereof and dental restoration material

    CN115028364A